Biopsable neural tissues: toward new biomarkers for Parkinson’s disease? - Lebouvier, Thibaud; Tasselli, Maddalena; Paillusson, Sébastien; Pouclet, Hélène; Neunlist, Michel; Derkinderen, Pascal (Frontiers in Psychiatry, 2010)
Biomarkers for Parkinson’s disease (PD) are mainly intended for the early diagnosis of the disease and to monitor its progression, two aspects insufficiently covered by clinical evaluation. In the last 20 years, the search for biomarkers has been supported by technological advances in the fields of molecular genetics and neuroimaging. Nevertheless, no fully validated biomarker is yet available, and there is still a need for biomarkers that will complement those already available. Development of biomarkers for PD has been hampered by the fact that the core pathology lies in the brainstem, hidden from direct study in living patients. In this context, the recent observations that clearly demonstrated the presence of PD pathology in peripheral neural tissues provide new opportunities to develop original histopathological markers of the disease. Some of these peripheral tissues, especially the enteric nervous system, by being assessable using routine biopsies, could represent a window to assess in vivo the neuropathological processes occurring in PD.